PERILAKU VERBAL WANITA DALAM INTERAKSI SOSIAL DI PUSAT- PUSAT PERBELANJAAN DI DAERAH ISTIMEWA YOGYAKARTA - -, Zamzani; Musfiroh, adkiroatun; Rahayu, Yayuk Eny (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
This article is about a study aimed at describing women's verbal behaviorin social interaction at shopping centers at the phonological, lexical, structural, andpragmatic levels and the factors influencing it.The results of the study can briefly be stated as follows. First, theirpronunciation tends to exhibit (a) high tones, (b) the occurrence of lengthening,and (c) a volume varying between loud and low. The factors acting as thebackground are (a) the organs of articulation, (b) cultural factors, (c) situationalcontexts, and (d) functions of utterances. Second, the vocabulary used is partlyhonorific in nature, chosen in the course of respecting their partners in theinteraction, especially in the use of salutations. Third, the structure of the languageused tends to undergo (a) deletions of certain parts considered already commonlyunderstood by the communication participants, (b) contractions in thepronunciation of certain words, and (c) occurrences of salutations at the end ofutterances. The factors acting as the background are (a) the setting of theinteraction, which involves spoken language used face-to-face so that thecommunication participants are in the same situational context, (b) the level offormality of the interaction, (c) the level of the participants' intimacy, and (d)honorific factors characteristic to women. Fourth, pragmatically implicatures tendto be used at certain times. A factor acting as the background is a culture of a highcontext and it functions as an indicator of the speaker's social status or level.Keywords : verbal behavior, social interaction, pronunciation, vocabulary,structure, pragmatic